Diseño de un Modelo Gestión en Mantenimiento para la empresa MOOG Medical Devices Group - Espinoza Alfaro, Carlos Alfredo (Instituto Tecnológico de Costa Rica, 2018)
The operational excellence that companies seek in this decade is due to the broad market and competition that currently exists, MOOG MDG is not the exception of this competition, so this organization is in the constant search to optimize production costs, safeguarding the quality that lies in the manufacturing process, meeting the needs of the end customer or consumer. To achieve this operational excellence, companies must have in the case of the Maintenance area, strategies that allow the equipment to be carried and maintained to the condition required by the business unit. It is from this point, where a Maintenance Management Model contributes as a key factor to achieve the goals and fulfill the objectives that seek the growth of the organization. Currently the organization tries to solve problems in sub lines of assembly of the main product which is the Enteral Feeding Set, for which the Maintenance Management Model developed in this project, from methodologies such as the Balanced Score Card that defines the necessary objectives, the application of the Maintenance Audit (MES) that determines the current condition of the department, the implementation of the criticality and equipment hierarchization (CTR) method that define the critical equipment that requires greater attention and resources, the use of Reliability Centered Maintenance (RCM) to detect the failure modes of critical equipment and propose proactive actions through Maintenance Plans, they achieve together, attack the current problem present in the organization by increasing the availability associated with the operational context.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018.
Keywords: Competencia; Costos; Optimización; Calidad; Estrategia; Gestión; Mantenimiento; Cuadro de Mando Integral; Auditoría; Research Subject Categories::TECHNOLOGY::Engineering mechanics